Platelet‐derived growth factor‐D and Rho GTPases regulate recruitment of cancer‐associated fibroblasts in cholangiocarcinoma. Issue 3 (22nd July 2013) - Cadamuro, Massimiliano; Nardo, Giorgia; Indraccolo, Stefano; Dall'Olmo, Luigi; Sambado, Luisa; Moserle, Lidia; Franceschet, Irene; Colledan, Michele; Massani, Marco; Stecca, Tommaso; Bassi, Nicolò; Morton, Stuart; et al.
<x xml:space="preserve">Abstract</x> Cholangiocarcinoma (CCA) is characterized by an abundant stromal reaction. Cancer‐associated fibroblasts (CAFs) are pivotal in tumor growth and invasiveness and represent a potential therapeutic target. To understand the mechanisms leading to CAF recruitment in CCA, we studied (1) expression of epithelial‐mesenchymal transition (EMT) in surgical CCA specimens and CCA cells, (2) lineage tracking of an enhanced green fluorescent protein (EGFP)‐expressing human male CCA cell line (EGI‐1) after xenotransplantation into severe‐combined‐immunodeficient mice, (3) expression of platelet‐derived growth factors (PDGFs) and their receptors in vivo and in vitro, (4) secretion of PDGFs by CCA cells, (5) the role of PDGF‐D in fibroblast recruitment in vitro, and (6) downstream effectors of PDGF‐D signaling. CCA cells expressed several EMT biomarkers, but not alpha smooth muscle actin (α‐SMA). Xenotransplanted CCA masses were surrounded and infiltrated by α‐SMA‐expressing CAFs, which were negative for EGFP and the human Y‐probe, but positive for the murine Y‐probe. CCA cells were strongly immunoreactive for PDGF‐A and ‐D, whereas CAFs expressed PDGF receptor (PDGFR)β. PDGF‐D, a PDGFRβ agonist, was exclusively secreted by cultured CCA cells. Fibroblast migration was potently induced by PDGF‐D and CCA conditioned medium and was significantly inhibited by PDGFRβ blockade with Imatinib and by silencing PDGF‐D expression in CCA cells. In fibroblasts, PDGF‐D activated the Rac1 and Cdc42 Rho GTPases and c‐Jun N‐terminal kinase (JNK). Selective inhibition of Rho GTPases (particularly Rac1) and of JNK strongly reduced PDGF‐D‐induced fibroblast migration. Conclusion: CCA cells express several mesenchymal markers, but do not transdifferentiate into CAFs. Instead, CCA cells recruit CAFs by secreting PDGF‐D, which stimulates fibroblast migration through PDGFRβ and Rho GTPase and JNK activation. Targeting tumor or stroma interactions with inhibitors of the PDGF‐D pathway may offer a novel therapeutic approach. (Hepatology 2013;53:1042–1053)